Design of an Optimum Massive MIMO FSO System and Analysis of its Performance in Different Weather Conditions (MIST International Journal of Science and Technology, 2022)
This aim of this work is to propose a massive MIMO FSO system with optimum design parameters and analyze its performance in various turbulent weather conditions by simulating the model in Optisystem 18.0. In recent years, the need for high speed data transfer for real time communication has become a necessity. Implementation of massive MIMO system has already gained remarkable achievement using the conventional RF transmission system. Although it is very much efficient in its application, it has some problems, such as licensing restrictions, bandwidth depletion, fragmentation. In this respect, Free space optics (FSO) is an efficient method for high speed data transfer as it does not have above limitations. Different researches conducted using MIMO FSO models have shown promising results. The use of massive MIMO system (more than 8×8 array of antennas) will enhance data rate further. In this research work, an optimum massive MIMO FSO system has been designed with 16×16 array of antennas. The performance of this system is analyzed in different weather conditions and compared with that of 8×8 system. The analysis of performance is done by power penalty and receiver sensitivity plots. A significant transmission range and an optimum performance is obtained by using this system at a data rate of 40 Gbps. However, data transmission rate can be much more enhanced in this system at the cost of reduced performance and a shorter transmission range.MIJST, Vol. 10, December 2022: 43-52DOI: https://doi.org/10.47981/j.mijst.10(03)2022.335(43-52)